Galaxy evolution across environments as probed by the ages, stellar metallicities, and [α /Fe] of central and satellite galaxies - Gallazzi, Anna; Pasquali, Anna; Zibetti, S.; Barbera, F. La (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT. We explore how the star formation and metal enrichment histories of present-day galaxies have been affected by environment combining stellar populatio